The role of nitric oxide in pulmonary arteriolar and left heart ventricle hypertrophy in chickens at sea level and exposed to high altitude hypoxia. - Vásquez C., María (2012)
The aim of this study was to determine the nitrites and nitrates concentration, stable metabolites of NO, and its correlation with the degree of pulmonary arteriole hypertrophy in chickens raised at environmental hypoxia. A total of 135 Cobb-Vantres male chickens, born at sea level were used. Of this, 60 chicks raised at sea level (SL), and 60 at high altitude (A), 3230 m above sea level; while the remaining 15 birds were slaughtered at 1 day of age. Fifteen 15 chicks per group were randomly selected and slaughtered at 10, 20, 30 and 40 days of age. It was determined body weight (BW), hematocrite (Ht), nitrites and nitrates, muscular wall/arteriolar diameter (CM/DA) ratio, right ventricle weight/total ventricle weight ratio (RV/TV), and right ventricle weight/body weight ratio (RV/BW) ratio. BW was greater at SL than at A (p< 0.05), whereas Ht was greater in A than at SL (p< 0.05). The nitrites and nitrates levels at SL were similar at all ages, whereas at A decreased at 20 days and increased at 30 days (p< 0.05). A process of muscularization in the pulmonary arterioles was observed in relation to age in both groups. The RV/TV and RV/BW ratios showed a right cardiac hypertrophy in chickens raised under hypoxia. There was a significant correlation between levels of nitrites and nitrates at different times of exposition to hypoxia with MW/AD, RV/TV and RV/BW ratios. It is concluded that variations in the production of NO directly affect the proliferation of smooth muscle of pulmonary arterioles conducing to a compensatory right cardiac hypertrophy.